Role of saposin C and D in auditory and vestibular function. (21st July 2015) - Lustig, Lawrence R.; Alemi, Sean; Sun, Ying; Grabowski, Gregory; Akil, Omar
Abstract : Objectives/Hypothesis: Saposins are small proteins derived from a precursor protein, prosaposin. Each of the four saposins (A–D) is necessary for the activity of lysosomal glycosphingolipid hydrolases. Individual saposin mutations lead to lysosomal storage diseases, some of which are associated with hearing loss. Here we evaluate the effects of the loss of saposins C and D on auditory and vestibular function in transgenic mice. Methods: Transgenic mice with either loss of saposin C function or a combined loss of saposin C + D function were studied. Light microscopy and immunofluorescence were used to evaluate histologic and morphologic changes in the auditory and vestibular organs. Acoustic brainstem response thresholds and distortion product otoacoustic emissions were used to study the auditory phenotype. Results: A null mutation of saposin C did not result in any identifiable histologic changes or loss of hearing through postnatal day 55. Combined losses of saposins C and D similarly did not result in any changes in organ of Corti histology or loss of hearing. However, inclusions within the vestibular end organs was noted, consistent with afferent and efferent neuronal sprouting, although to a much milder degree than seen in the previously studied prosaposin knockout mouse. Conclusions: Loss of saposin C and D function, although causing mild phenotypic changes in the vestibular end organs, otherwise results in minimal functional impairment and no changes in the auditory system. It is more likely that the auditory and vestibular effects of the loss of prosaposin are mediated through the actions of saposin A and/or B. Level of Evidence: NA. Laryngoscope, 126:452–459, 2016